The Unexplored Role of Intra-articular Adipose Tissue in the Homeostasis and Pathology of Articular Joints - Labusca, Luminita; Zugun-Eloae, Florin (Frontiers in Veterinary Science, 2018)
Intraarticular adipose tissue deposits known as articular fat pads (AFP) are described to exist within synovial joints. Their assumed role in normal joint biomechanics is increasingly objectivized by means of advanced methods of functional imaging. AFP possess structural similarity with body subcutaneous white adipose tissue (WAT) however seems to be regulated by independent metabolic loops. AFP dimension are conserved during extreme WAT states: obesity, metabolic syndrome, lipodystrophy and cachexia. Hoffa fat pad (HFP) in the knee is increasingly recognized as a major player in pathological joint states such as anterior knee pain and osteoarthritis. HFP contains numerous population of mesenchymal and endothelial progenitors however the possible role of mature adipocytes in the maintenance of stem cell niche is unknown. We propose that AFP is an active component of the joint organ with multifunctional roles in the maintenance of joint homeostasis. Endowed with a rich network of sensitive nervous fibbers, AFP may act as a proprioceptive organ. Adipokines and growth factors released by AFP-resident mature adipocytes could participate in the maintenance of progenitor stem cell niche as well as to local immune regulation. AFP metabolism may be locally controlled, correlated with but independent of WAT homeostasis. The identification of AFP role in normal joint turnover and its possible implication in pathological states could deliver diagnostic and therapeutic targets. Drug and/or cell therapies that restore AFP structure and function could become the next step in the design of disease modifying therapies for disabling joint conditions such as osteoarthritis and inflammatory arthritis.